Sex differences in red blood cell α ‐synuclein protein and its heteroaggregates with amyloid‐β and tau in early Alzheimer's disease: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - Prete, Eleonora Del; Daniele, Simona; Giampietri, Linda; Galgani, Alessandro; Piccarducci, Rebecca; Gerfo, Annalisa Lo; Petrozzi, Lucia; Cavallini, Chiara; Pietrobono, Deborah; Trincavelli, Maria Letizia; Frosini, Daniela; Siciliano, Gabriele; et al.
Abstract: Background: A growing interest is recently focused on sex‐related differences in Alzheimer's Disease (AD) pathology to optimize patients stratification and to personalize treatment. Among markers that are expression of this neurodegenerative disease, red blood cells (RBCs) levels of α‐synuclein (α‐syn) and its heterocomplexes with amyloid‐β (Aβ) and tau have been proposed as peripheral biomarker of AD. The aim of our study was to explore sex differences in RBC levels of α‐syn and its heterocomplexes in a group of AD/ mild cognitive impairment due to AD (MCI‐AD) patients and of Healthy Controls (HC). Method: Differences between male and female sex matched for age were investigated in RBC regarding homo‐ and heteroaggregates of α‐syn, Aβ and tau [total tau (t‐tau), Aβ42, total α‐syn (t‐ α‐syn), oligomeric α‐syn (o‐α‐syn), α‐syn/Aβ and α‐syn/tau] in a cohort of AD/MCI‐AD patients in early stages of disease and in HC. Result: In our study 147 subjects were enrolled, 47 AD, 40 MCI‐AD and 60 HC. In AD/MCI‐AD cohort we identified significant differences in t‐tau levels between sex (p=0.010), with higher value in men than women (6.1±5.9ng/mg vs 4.0±6.8ng/mg), no significant differences Aβ42, t‐α‐syn, o‐α‐syn, α‐syn/Aβ and RBC‐α‐syn/tau. In HC group we reported significant differences in Aβ42 (p=0.014) and α‐syn/tau (p=0.030). In particular, women presented higher Aβ42 and α‐syn/tau compared to men (18.22±12.19 ng/mg vs 13.31±13.86 ng/mg and 2.93±1.67 ng/mg vs 1.95±1.75 ng/mg, respectively). Mean age for the group AD/MCI‐AD was 72.5±6.61yy for women and 71.9±6.43 yy for men, while mean age was 62.38±8.48 yy for women and 66.20 yy for men in HC group. Comparison in biomarkers between AD/MCI‐AD and HC was not performed due to significant differences between age p<0.001 in women and p=0.003 in man. Conclusion: Sex differences in RBC biomarkers for AD were identified in AD/MCI‐AD patients and in HC. Women reported higher levels of RBC Aβ42 and RBC α‐syn/tau than men in HC, while RBC t‐tau concentrations were higher in men than in women in AD/MCI‐AD cohort. Although additional investigations in larger samples are needed to confirm our data, a different distribution of neurodegenerative biomarkers in men and women is likely.